(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The review & discussion of research articles, journals, and some books help us to understand dementia. This review article may help to understand What is dementia? How to prevent dementia? What care we should take to minimize the possibility of dementia? The number of dementia patients is increasing day by day. Dementia is very common in old age. At least 7% of geriatric people aged 60 and above are suffering from dementia. The multitude of geriatric people including those with dementia is arising and the adolescent/teenager people death rate is reducing. Dementia is an unusual part of getting old. The common risk factors of dementia might be physically inactive, excessive alcohol intake, depression, hypertension, illiteracy, unable to hear, social isolation, smoking, diabetes, traumatic brain injury, chronic stress, etc. Dementia is not only caused due to risk factors but also it causes because of genetic, clinical, and neurological characteristics. About 50-80% of dementia cases are suffered because of Alzheimer's Disease. Alzheimer's disease and further neurodegenerative disorders begin sometime before the clinical symptoms appearing. Alzheimer's Disease, Parkinson's Disease, Psychiatric Disorders, Vascular Dementia, and other neurodegenerative diseases like Lewy Body Dementia and Frontotemporal Dementia are also common causes of dementia. Some types of dementia are common in first-degree relatives e.g. Frontotemporal dementia (FTD). Geriatric people suffer from dementia because of the degenerative changes in the brain which occur during aging. Only 25-40% of moderate-stage dementia is acknowledged in primary care. Patients suffering from dementia normally reject the fundamental independence accessible to normal people. Till now dementia prevention, intervention, and care will significantly improve living and dying for the benefit of a patient suffering from dementia and their families, and thus society.